The extraction of gold from sulphidic concentrates by roasting and cyanidation (The Southern African Institute of Mining and Metallurgy, 1988)
The refractoriness of the gold in many of the pyritic ores from the eastern Transvaal is due mainly to the association between the gold and the sulphides, but it can be due to the presence of graphltlc carbonaceous material, which complicates the recovery of the gold by virtue of its adsorption activity. In an examination of the roasting characteristics of three flotation concentrates from the Barberton area, It was found that the gold in the concentrates occurred mostly in two forms: in very fine gold particles distributed within the arsenopyrite, and in a slightly coarser form loosely associated with the pyrite. Direct cyanidation of the concentrates gave gold extractions of from 16 to 30 per cent. After the concentrates had been roasted at temperatures of 650 to 700°C for 20 minutes with rabbling, the extractions varied from 86 to over 90 per cent. Examination of the residues after cyanidation indicated that gold was present in the porous calcines or in the calcined sulphide product. This observation, together with porosity measurements, suggests that physical encapsulation of the gold particles is the main reason for the refractory behaviour of the gold in the calcines.